2016
DOI: 10.1074/jbc.m116.754069
|View full text |Cite
|
Sign up to set email alerts
|

The Polyadenosine RNA-binding Protein, Zinc Finger Cys3His Protein 14 (ZC3H14), Regulates the Pre-mRNA Processing of a Key ATP Synthase Subunit mRNA

Abstract: Polyadenosine RNA-binding proteins (Pabs) regulate multiple steps in gene expression. This protein family includes the well studied Pabs, PABPN1 and PABPC1, as well as the newly characterized Pab, zinc finger CCCH-type containing protein 14 (ZC3H14). Mutations in ZC3H14 are linked to a form of intellectual disability. To probe the function of ZC3H14, we performed a transcriptome-wide analysis of cells depleted of either ZC3H14 or the control Pab, PABPN1. Depletion of PABPN1 affected ϳ17% of expressed transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 91 publications
0
33
0
Order By: Relevance
“…Transcript levels were normalized to input and then to IgG control. Using a candidate-based approach, we tested for enrichment of RNA targets using a previously identified ZC3H14 target transcript Atp5g1 ( 9 ) and other important neuronal transcripts with potential links to ZC3H14 (unpublished results), Psd95 ( Dlg4 ) and Mapt . The Atp5g1, Psd95 and Mapt mRNA are all significantly enriched in ZC3H14, THOC5 and ALYREF precipitations as compared to the IgG control (Figure 4B – D ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcript levels were normalized to input and then to IgG control. Using a candidate-based approach, we tested for enrichment of RNA targets using a previously identified ZC3H14 target transcript Atp5g1 ( 9 ) and other important neuronal transcripts with potential links to ZC3H14 (unpublished results), Psd95 ( Dlg4 ) and Mapt . The Atp5g1, Psd95 and Mapt mRNA are all significantly enriched in ZC3H14, THOC5 and ALYREF precipitations as compared to the IgG control (Figure 4B – D ).…”
Section: Resultsmentioning
confidence: 99%
“…Like Nab2, ZC3H14 is primarily localized to the nucleus and both Nab2 and ZC3H14 bind with high affinity to polyadenosine RNA ( 15 , 16 ). Although Nab2 and ZC3H14 bind to polyadenosine RNA tracts ( 17 ) and therefore could bind to all mRNA transcripts, previous work has shown that loss of ZC3H14 only alters the steady-state levels of a small number of transcripts ( 9 ). This finding focuses the regulation of mRNA processing by ZC3H14 to a select group of transcripts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear samples were incubated on ice for 20 min and then centrifuged for 10 min at 15,600 × g . The supernatant (nuclear fraction) was separated from the pellet ( 34 ). After preclearance with protein G-Sepharose (GE Healthcare), the lysates were incubated with anti-Arid5a or anti-IgG at 4 °C for 8 h. The resin was washed three times with RNA immunoprecipitation buffer (50 mM Tris⋅HCl pH 7.4, 100 mM NaCl, and 0.5% Nonidet P-40 in diethylpyrocarbonate-treated water).…”
Section: Methodsmentioning
confidence: 99%
“…59,63,75 Finally, the zinc-finger protein ZC3H14, a human homolog of Nab2p, was recently ascribed an RNA protective function, 76 and like Nab2p, ZC3H14 was suggested to control poly(A) tail length and modulate processing of pre-mRNAs. 77 An additional degradative role in RNA maturation has also recently been ascribed to PABPN1. Interestingly this occurs in a PAXT-independent manner and instead of the nuclear exosome involves the poly(A)-specific ribonuclease PARN.…”
Section: Poly(a) Binding Proteins (Pabps) In Rna Metabolismmentioning
confidence: 99%